Catalase Enhances Growth and Biofilm Production of Mycoplasma pneumoniae - Simmons, Warren L. (Curr Microbiol, 2015)
Mycoplasma pneumoniae causes chronic respiratory disease in humans. Factors thought to be important for colonization include the ability of the mycoplasma to form a biofilm on epithelial surfaces and the production of hydrogen peroxide to damage host tissue. Almost all of the mycoplasmas, including M. pneumoniae, lack superoxide dismutase and catalase and a balance should exist between peroxide production and growth. We show here that the addition of catalase to cultures enhanced the formation of biofilms and altered the structure. The incorporation of catalase in agar increased the number of colony-forming units detected and hence could improve the clinical diagnosis of mycoplasmal diseases.